Factors Affecting Organic And Non-Organic Rice Production In Muara Bulian District Batanghari Regency - S, Hariono (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2022)
This study aims to determine 1) the factors that influence the production of organic and non-organic lowland rice in Muara Bulian District, 2) to determine the income and income received by organic and non-organic rice farmers in Muara Bulian District. The object of this research is farmers who cultivate organic and non-organic rice in Muara Bulian District, Batanghari Regency. The data used in this study are primary data and secondary data. The sampling method used a census and purposive selection of research areas. Data analysis used multiple regression analysis. The results showed that the factors that significantly affect the production of organic and non-organic lowland rice were four variables, namely fertilizer (X4), seeds (X1), labor (X5) and pesticides (X3). The average income received by organic rice farmers is Rp. 21,402,500 while non-organic rice farmers are Rp. 16,654,761. The income received by organic rice farmers is Rp. 17,879,913.6 while non-organic rice farmers are Rp. 13,089,941.3. The income and income of organic rice farmers is greater than that of non-organic rice farmers. So it is concluded that the existing production factors affect the production of organic and non-organic lowland rice in Muara Bulian District, Batanghari Regency. The income and income of organic rice farmers is greater than that of non-organic rice farmers. So it is concluded that the existing production factors affect the production of organic and non-organic lowland rice in Muara Bulian District, Batanghari Regency. The income and income of organic rice farmers is greater than that of non-organic rice farmers. So it is concluded that the existing production factors affect the production of organic and non-organic lowland rice in Muara Bulian District, Batanghari Regency.